Investigating the role of alexithymia on the empathic deficits found in schizotypy and autism spectrum traits. (April 2015) - Aaron, Rachel V.; Benson, Taylor L.; Park, Sohee
Highlights: Schizotypal and autism traits were associated with increased alexithymia. Schizotypal and autism traits were associated with abnormalities in empathy. Alexithymia contributes uniquely to empathic deficits in these populations. Abstract: Alexithymia, the inability to identify and describe one's emotional experience, is elevated in many clinical populations, and related to poor interpersonal functioning. Alexithymia is also associated with empathic deficits in individuals with autism spectrum disorders. Accordingly, a better understanding of alexithymia could elucidate the nature of social-cognitive deficits transdiagnostically. We investigated alexithymia and components of empathy in relation to schizotypal and autism spectrum traits in healthy college students. Specifically, we examined higher-order components of empathic processing that involve perspective taking and other-oriented concern, which are reduced in alexithymia. Higher-order empathic processing was inversely correlated with both schizotypal and autism spectrum traits. Bootstrapping techniques revealed that alexithymia had a significant indirect effect on the relationship between higher-order empathy and these personality traits; thus, alexithymia contributes uniquely to their relationship. These findings suggest alexithymia represents one possible mechanism for the development of empathic deficits in these populations. These results are consistent with the perspective that awareness of one's own emotional state may predicate a successful empathic response to another's. This work highlights the importance of a consideration of alexithymia in elucidating the nature of empathic deficits in various clinical populations, and points to a potential point of social intervention.